An approach to determine tool damage in friction stir welding by linear damage accumulation - Sennewald, M.; Eisbrenner, R.; Hasieber, M.; Rohe, M.; Bergmann, J. P. (Welding in the world, 2025)
In addition to the unique weld seam properties, friction stir welding (FSW) includes specific challenges such as comparatively high static and dynamic forces and torque during welding. In the literature review to date, the design of the tools is mostly based on empirical values, which can result in over- and undermatching. The aim of this study is to systematically analyze the dynamic tool damage and the respective failure mechanisms in relation to the tool dimensions and process temperature, accounting for weld seam length and quality. The determination of partial tool damage enables classification of the maximum tolerable tool life, considering the impact of process temperatures on permissible stresses of FSW tools made of H13 steel. The results indicate that dynamic stresses can be significantly affected by rotational speed and welding speed. Linear damage accumulation was used to predict the maximum tolerable tool life by summing up partial damage over time, which has never been used in the context of friction stir welding on the basis of experimental measurement data. For this purpose, forces and torques were converted into stresses on the probe and initially compared with analytically determined S–N curves for the main stresses during welding. Although the resulting weld seam lengths currently indicate a clear overestimation of the tool life, they allow for an estimation of the tool damage depending on the used probe diameter and welding speed. Particularly when a rotational speed of 2500 min −1 is considered, an eleven times overestimation of tool life results for the 5 mm probe and eight times for the 6 mm probe. The most favorable outcomes were observed when the 5 mm probe was operated at 4000 min −1 , with an estimated tool life of 238 m and an experimental result of 213 ± 35 m, as an exact determination of the tool life was possible in this instance. A sensitivity analysis with regard to the recording frequency demonstrates a strong dependence on the pre-processing of the measurement data. For instance, adjusting the recording frequency and using a Butterworth low-pass filter enhances the prediction by approximately 47% (6 mm probe at 2500 min −1 ). The incorporation of experimentally determined S–N curves could further enhance the precision of the prediction in the course of further investigations. The experiments were carried out with a force-controlled robotized welding setup from Grenzebach Maschinenbau GmbH in which AA 6060 T66 sheets with a thickness of 5 mm were joined.